Tropics of tenderness eroticism in Hiligaynon folk poetry - Ong, Timothy (2021)
If colonial discourse is taken to mean as dominant in studying the tropics, the folk is that which is constantly effaced by this dominance. However, this effacement is not completely triumphant primarily because it is the folk which resides in the residue, the discourse that remains in the margins. This paper attempts to discuss key philological terms that relate to the tropicality of eroticism as it pertains to Hiligaynon folk poetry, but specific attention is given on the level of the lyric tradition. In this paper, I want to struggle with the structure of the riddle and proverb, as paktakun and hurubaton, respectively, if only to extract insights regarding their capacity to point towards the tropical condition that is characterized by excess as well as the eroticism embedded in the poetic form of the paktakun and hurubaton. More than claiming the content as erotic, as we shall see later on, I argue that the very forms of the paktakun and hurubaton lend themselves very well to a discussion of eroticism insofar as the logic contained in the Hiligaynon folk tradition is concerned. I then want to pursue this thought further in the sustained lyricism in the verses of Hiligaynon folk songs, and how the lyric form ferries the idea of erotic excess in the form of tropical speciations of Eros, specifically mingaw and gugma. The paper follows a philological trajectory in analyzing the tropicality of such erotic concepts, and how these are central in understanding the poetics of Hiligaynon folk sensibility.
Keywords: Epic poetry; Philippine poetry -- History and criticism